The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9053799
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling Vector Approximate Message Passing

Abstract: Recently proposed Vector Approximate Message Passing (VAMP) demonstrates a great reconstruction potential at solving compressed sensing related linear inverse problems. VAMP provides high per-iteration improvement, can utilize powerful denoisers like BM3D, has rigorously defined dynamics and is able to recover signals sampled by highly undersampled and ill-conditioned linear operators. Yet, its applicability is limited to relatively small problem sizes due to necessity to compute the expensive LMMSE estimator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Thus, we have a well-defined γ t t = γ t and γ τ = 0, τ < t for CG-VAMP. Lastly, the linear update f L with F t (Z t ) in WS-CG-VAMP also fits into the model (72) as shown in Theorem 3 in [20]. Thus, the result (75) holds for MF-OAMP, VAMP, CG-VAMP and WS-CG-VAMP.…”
Section: Appendix Bsupporting
confidence: 54%
See 2 more Smart Citations
“…Thus, we have a well-defined γ t t = γ t and γ τ = 0, τ < t for CG-VAMP. Lastly, the linear update f L with F t (Z t ) in WS-CG-VAMP also fits into the model (72) as shown in Theorem 3 in [20]. Thus, the result (75) holds for MF-OAMP, VAMP, CG-VAMP and WS-CG-VAMP.…”
Section: Appendix Bsupporting
confidence: 54%
“…The first group of algorithms, which we refer as OAMPbased algorithms, constructs f D and f L such that their output errors are asymptotically orthogonal to their input errors [10]. This group of algorithms includes Match Filter OAMP (MF-OAMP) [10], [27], VAMP [9], [24], CG-VAMP [25], [19], [20], WS-CG-VAMP [19] and others. Here the structure of the function…”
Section: A Oamp-based Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if the approximation produced by CG is sufficiently bad, then v t,i A→B might even increase with respect to v t−1 A→B . Based on numerical experiments in the current and the previous work [32], we have observed that the number of the inner-loop iterations sufficient to achieve a certain reduction of v t,i A→B per-outer-loop iteration significantly changes with t and therefore motivates the benefit in the adaptive choice of i[t] at each t.…”
Section: Adaptive Cg In Cg-vampmentioning
confidence: 89%
“…Practical estimation of v t,i A→B in CG-VAMP Next, we propose an asymptotically consistent estimator for the variance v t,i A→B that can be naturally implemented within CG and has negligible computational and memory costs. For this, we expand the result (32) and use the identity (18) to obtain v t,i A→B a.s.…”
Section: Stable Implementation Of Cg-vampmentioning
confidence: 99%